Технология реставрации арочных конструкций и сводов. Оценка значимости влияющих факторов - Осипов, С. А. (Ways to Improve Construction Efficiency, 2014)
The article discusses assessment of the importance of the formed groups of factors influence the choice of technology for the restoration of the arches and arched constructions of monuments of architectural, as well as its results.